Future directions in international financial integration research - A crowdsourced perspective - Lucey, Brian M.; Vigne, Samuel A.; Ballester, Laura; Barbopoulos, Leonidas; Brzeszczynski, Janusz; Carchano, Oscar; Dimic, Nebojsa; Fernandez, Viviana; Gogolin, Fabian; González-Urteaga, Ana; Goodell, John W.; Helbing, Pia; et al. (Elsevier, 2018)
This paper is the result of a crowdsourced eﬀort to surface perspectives on the present and future direction of international ﬁnance. The authors are researchers in ﬁnancial economics who attended the INFINITI 2017 conference in the University of Valencia in June 2017 and who participated in the crowdsourcing via the Overleaf platform. This paper highlights the actual state of scientiﬁc knowledge in a multitude of ﬁelds in ﬁnance and proposes diﬀerent directions for future research.
Keywords: financial economics; crowdsourcing; literature review; financial research; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|